Collective identity in the age of globalisation - Magdalena Bobro (The Person and the Challenges. The Journal of Theology, Education, Canon Law and Social Studies Inspired by Pope John Paul II)
This article deals with the legal liability of collective person in the age of globalization. It touches the problem of the “person” in such fields as law, philosophy and sociology. The article presents the influence of globalisation on identity and the question of indi- vidualisation. Identity is defined as a process of internal and external adjustment. The processes of globalisation may contribute to the loss of cultural identity. The diverse nature of globalisation has given rise to new identities. Concurrently, the article also presents the challenges posed by globalisation, for instance: identity and freedom of in- dividualisation versus community and belonging. The author aims to make a short analysis according to the liability of collective persons throughout the history of civil and criminal law.